Correlations of crystal shape and lateral orientation in bioinspired CaCO3 mineralization. Issue 35 (17th August 2018) - Liu, Ming-Feng; Lu, Zihao; Zhang, Zhisen; Xiao, Chuanlian; Li, Ming; Huang, Ya-Xi; Liu, Xiang Yang; Jiang, Yuan
Abstract : Our study shows that in bioinspired mineralization, the crystal shape and lateral orientation are highly correlated instead of being independent. Abstract : For bioinspired crystalline materials, both the shape and orientation play key roles in determining their structural functions and application opportunities. Though there have been numerous studies on this topic, few studies of bioinspired mineralization nevertheless focus on the correlation between the shape control of the crystalline products and their lateral orientation. The current study targets the shape control of lateral CaCO3 crystals on a substrate – poly(ε-caprolactone) (PCL) by taking advantage of the synergetic effect of the lateral orientation degree of PCL and the concentration of the additive – poly(acrylic acid) (PAA). Single crystalline microrods with lateral orientational preference are only obtained on PCL thin films that are highly ordered in the lateral orientation. It is worth noting that the shape of the abovementioned microrods, denoted by their aspect ratios, is largely determined by the concentration of PAA. The decrease of the lateral orientation ordering of the PCL thin film transforms single crystalline microrods to polycrystalline products, regardless of the concentration effect of PAA. Moreover, the kinetic study confirms that the shape-anisotropy of the single crystalline microrods starts to appear in the lateral crystal growth stage – the last step of the multistage mineralization process. This study, for the first time, highlights the strong correlations between the crystal shape and lateral orientation in bioinspired CaCO3 mineralization, which is pivotal for the rational structural control in crystal engineering a broad spectrum of functional and engineered materials.